Effectiveness of mindfulness training in fostering tobacco cessation among undergraduates in a Nigerian university (2012)
The study investigated the impact of mindfulness training in fostering tobacco cessation among undergraduates in a Nigerian university, it also observed the moderating effect of self-efficacy on the causal link between mindfulness training and tobacco cessation. Participants were 57 students randomly assigned to experimental and control groups. A pre-test, post-test, design was utilized. The experimental group was exposed to a 12 week mindfulness training programme. Participants in both experimental and control groups were tested before and after training programme on tobacco cessation. Data collected were analysed using analysis of covariance (ANCOVA). Results showed that the experimental group improved significantly in tobacco cessation than the control group. Further, self-efficacy mediated effectively the causal link between mindfulness training and tobacco cessation among the participants. It was recommended that Mindfulness training should be introduced in smoking cessation programmes and advancing studies in smoking cessation.